Modelling the cost-effectiveness of cervical cancer screening with HPV self-sampling and molecular triage for women aged 60–69 years - Fridljung, Jasmine; Bergengren, Lovisa; Ryen, Linda; Lillsunde Larsson, Gabriella (Discover. Oncology, 2025)
Background Since 2022, self-sampling has been recommended in Sweden’s cervical screening program. Despite still being used primarily for long-term non-attendees, its expected increase in use raises interest in molecular triage methods applicable to self-collected samples. Postmenopausal women face screening challenges due to physiological changes, making this group particularly relevant for evaluating alternative strategies. This study models the cost-effectiveness of different sampling and triage methods in identifying histological high-grade squamous intraepithelial lesions (HSIL) in women aged 60–69 years. Methods Using real-world data, this study compares the cost-effectiveness of currently implemented strategy based on professional HPV sampling and combination triage with genotyping and cytology, with modelled strategies based on self-sampling and various molecular triage. The comparison evaluates healthcare resource use and the number of identified histological HSIL cases. The analysis focuses on a single screening cycle, re-testing of invalid samples or screening-positive/triage-negative women are not addressed. Results Screening with molecular triage either leads to decreases in effect, i.e. fewer histological HSIL identified, or significant cost increases due to higher rate of HPV-positive screening samples and higher number of colposcopy follow-ups. Conclusions Molecular triage, whether used with self-sampling or professional sampling, does not appear cost-effective for identifying HSIL in this age group compared to the current screening strategy.